СИСТЕМА ВПРАВ У ПРОЦЕСІ ПРОФІЛЬНОГО НАВЧАННЯ СТАРШОКЛАСНИКІВ ТЕХНОЛОГІЯМ ВИРОБНИЦТВА (Педагогіка вищої та середньої школи, 2008)
The article deals with some aspects of improving special training for the teachers of labour discipline for teaching the senior students the technologies of production in the secondary schools.